(untitled) (Journal of Forensic Medicine & Toxicology, 2024)
There are 3500 species of snakes, of which 250 are venomous. In India about 216 species, of which 52 are poisonous. World Health Organization records more than 2.5 million venomous snake bites worldwide each year with more than125000 deaths. India records about 2,00,000 bites of which 15000 end in deaths. Snake venoms can be classified as hemotoxic, neurotoxic, or cytotoxic and they can all act together involving multiple tissues and organs. Mortality due to poisonous snakebite is an emerging public health concern. In India snakebite deaths are unnatural deaths. So, they are medicolegal cases that need to be examined at autopsy according to statutory rules. In many cases history of bite might not always be consistent. Internal findings at autopsy in fatal snakebite cases are often non-specific. Suspicious and unknown bites are also difficult to diagnose and establish at autopsy. Snakebite induced changes in various organs are documented in literature. Some authors have tried to develop a scoring system on the basis of the renal pathology found at autopsy in fatal snakebite cases to differentiate between neurotoxic and haemotoxic bites. Histological changes in the organs that are primary targets by the snake venom may help and guide the pathologist and physician in their early intervention. Here, we present post-mortem histopathological findings of 2 cases of snake bite.